Family Counseling Outreach Regarding Parenting Patterns in Kaplongan Village, Karangampel, Indramayu - Nica Widyaningsih (Annujum: Journal of Humaniora and Law, 2025)
This community service, entitled Family Counseling Outreach Regarding Parenting Patterns in Kaplongan Village, Karangampel Indramayu, aims to ensure that parents in Kaplongan Village have the desire to gain more insight into the development of parenting patterns in the present and carry out the function of parents in forming a family. the good one. The approach used in implementing this activity program is a descriptive analytical approach, which is an approach to describe or provide an overview of the object under study through data or samples that have been collected as they are without carrying out analysis and making conclusions that apply to the general public. To find facts in the field by interviewing and observing the people of Kaplongan Village. Data analysis in this program uses qualitative descriptive methods. In field research, collect all data from interviews as the main data from informants. The result of this community service activity is the importance of increasing the knowledge and skills of parents in carrying out the care, upbringing and education of children in their own family on the basis of good character and increasing community capabilities.